Evaluation of Marketing Strategies for Educational Services in Increasing Public Interest - Safaat; Leonard Adrie Manafe (International Journal of Business and Applied Economics, 2023)
Education today is a necessity for every individual, society, and government. A marketing strategy is a plan carried out by the company in order to achieve its goals. These goals are determined by three elements: consumers, satisfaction, and the marketing mix. Marketing in educational institutions aims to provide information to the public about educational products and differentiate school products from those of other madrasas. This research is a type of qualitative research. The informants in this study were four people, consisting of the principal, vice principal of student affairs, parents of students, and the community around the MINU Tambaksumur Madrasah. The marketing strategy carried out by the MINU Tambaksumur Madrasah is good, boasting several indicators, namely madrasah promotion through social media, excellent programs, student achievement, tuition fees, school infrastructure, learning methods, and learning media used.